2017
DOI: 10.1175/jcli-d-16-0570.1
|View full text |Cite
|
Sign up to set email alerts
|

Land Surface Precipitation in MERRA-2

Abstract: The Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2), features several major advances from the original MERRA reanalysis, including the use, outside of high latitudes, of observations-based precipitation data products to correct the precipitation falling on the land surface in the MERRA-2 system. The method for merging the observed precipitation into MERRA-2 has been refined from that of the (land-only) MERRA-Land reanalysis. This paper describes the method and evaluates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
234
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 310 publications
(262 citation statements)
references
References 44 publications
10
234
0
Order By: Relevance
“…While M2 appears to follow a similar annual trend in the time series as ML, M2 is 33% higher than ML during the years 2006-2010. It implies that when compared to ML, a merged satellite-gauge precipitation product M2 was improved by its precipitation correction algorithm (Reichle et al, 2017). The other three datasets CH, TM, and TR agree well with annual rates within the range of the two MERRA precipitation products.…”
Section: Comparison Of Model Precipitation Estimatesmentioning
confidence: 83%
See 2 more Smart Citations
“…While M2 appears to follow a similar annual trend in the time series as ML, M2 is 33% higher than ML during the years 2006-2010. It implies that when compared to ML, a merged satellite-gauge precipitation product M2 was improved by its precipitation correction algorithm (Reichle et al, 2017). The other three datasets CH, TM, and TR agree well with annual rates within the range of the two MERRA precipitation products.…”
Section: Comparison Of Model Precipitation Estimatesmentioning
confidence: 83%
“…Previous studies Huffman et al, 2007;Reichle et al, 2017) have already demonstrated that by incorporating in situ observation, precipitation datasets CHIRPS, MERRA-2, TMPA3B42 are better than CHIRP, MERRA-Land, TMPA3B42RT, respectively. Besides, ground observations are generally point data whereas these satellite-and/or model-based precipitation datasets represents averages in large scale.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The 2 m T a in NCEP-1, NCEP-2, MERRA, MERRA-2, ERA-20C, ERA-20CM, CERA-20C, NOAA 20CRv2c, NOAA 20CRv2 and CFSR are model-derived fields that are functions of the surface skin temperature, the temperature at the lowest model level, the vertical stability and the surface roughness, which are constrained primarily by observations of upper-air variables and the surface pressure (Kanamitsu et al, 2002;Rienecker et al, 2011;Reichle et al, 2017;Poli et al, 2016;Hersbach et al, 2015;Laloyaux et al, 2016;Compo et al, 2011;Saha et al, 2010). However, the T a in ERA-Interim and JRA-55 are post-processing products by a relatively simple analysis scheme between the lowest model level and the surface and are analysed using ground-based observations of T a , with the help of Monin-Obukhov similarity profiles consistent with the model's parameterization of the surface layer (Dee et al, 2011b;Kobayashi et al, 2015).…”
Section: Reanalysis Productsmentioning
confidence: 99%
“…These reanalyses include the first two generations of global reanalyses produced by the National Centers for Environmental Prediction, NCEP-R1 (Kalnay et al, 1996) and NCEP-R2 (Kanamitsu et al, 2002); the reanalyses produced by the European Centre for MediumRange Weather Forecasts (ECMWF), ERA-15 (Gibson et al, 1997), ERA-40 (Uppala et al, 2005) and ERA-Interim (Dee et al, 2011b); the Japanese Meteorological Agency, JRA-25 (Onogi et al, 2007) and JRA-55 (Kobayashi et al, 2015); and the National Aeronautics and Space Administration, the Modern-Era Retrospective Analysis for Research and Applications (MERRA) (Rienecker et al, 2011) and its updated version, MERRA-2 (Reichle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%